Maladies chroniques et travail - Dominique Lhuilier; Anne-Marie Waser (Perspectives Interdisciplinaires sur le Travail et la Santé)
The two qualitative studies presented here focus on the working life of 106 chronically ill people (cancer or HIV) who may or may not have stopped working during the care process. We analysed their activities and the evolution of their individual strategies, especially their work relationships with their colleagues or superiors. We then showed that the resources used to manage risky health situations, continued employment, and the quality of work relationships were linked to several factors, namely the marks left by the disease and treatment, social status, and the various cases of assimilation, integration, maintenance, and differentiation in the people’s work styles and their working environments. Life with a disease is a changed life that is conscious of its vulnerability and permeated by an ongoing dialectic between forces of exclusion and re-creation.